2012
DOI: 10.1111/j.1559-1816.2012.00927.x
|View full text |Cite
|
Sign up to set email alerts
|

Rejection Sensitivity, Social Withdrawal, and Loneliness in Young Adults

Abstract: Rejection sensitivity (RS) has significant negative impacts on individuals' social cognitions, feelings, and interpersonal behaviors. The present research assessed the hypothesis that the effect of RS on young adults' loneliness is mediated by their tendency to withdraw from social contact so as to avoid possible rejection. Participants completed measures of their RS, their tendencies to engage in social withdrawal to avoid rejection, and their loneliness; as well as measures of their social avoidance and dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(125 citation statements)
references
References 60 publications
10
114
0
1
Order By: Relevance
“…Social difficulties, including loneliness, isolation, are also often indicated in suicidal behavior among college students including diverse college students (Chang et al, 2010;Jeglic et al, 2007). We included rejection sensitivity, a social cognitive-affective processing style linked to but not completely correlated with identified interpersonal triggers (current loneliness, isolation) of suicidal behavior in college students (Watson & Nesdale, 2012). Future studies could thus also include measures of binge drinking and current social support and connection.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Social difficulties, including loneliness, isolation, are also often indicated in suicidal behavior among college students including diverse college students (Chang et al, 2010;Jeglic et al, 2007). We included rejection sensitivity, a social cognitive-affective processing style linked to but not completely correlated with identified interpersonal triggers (current loneliness, isolation) of suicidal behavior in college students (Watson & Nesdale, 2012). Future studies could thus also include measures of binge drinking and current social support and connection.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The role of perceived social support as a buffer and protective barrier to loneliness has been well documented [91][92][93]. Infidelity is known to destroy a person's social support system as a result of no longer having access to resources that would help them cope with the stressors associated with the devastating situation [86].…”
Section: Infidelity: Social Support and Lonelinessmentioning
confidence: 99%
“…Evidence from adult studies demonstrates increased vigilance to social cues in lonely people. In Table 1, we provide an overview of these findings, which shows that loneliness in (young) adulthood is associated with remembering more social events , enhanced attention to facial and vocal expressions of emotion Pickett, Gardner, & Knowles, 2004), greater activation of the visual cortex in response to unpleasant social pictures of people compared with objects ( J. T. Cacioppo, Norris, Decety, Monteleone, & Nusbaum, 2009), initial visual vigilance to pictures depicting social rejection (Bangee, Harris, Bridges, Rotenberg, & Qualter, 2014), and sensitivity to signs of rejection and fear of negative evaluation ( Jackson, 2007;Watson & Nesdale, 2012). Studies with lonely children and adolescents have shown them to have difficulty disengaging from rejection stimuli during an eye-tracker task and have highlighted their sensitivity to signs of rejection ( Jackson, 2007;.…”
Section: The Cognitive Reaffiliation Process Across Ontogenymentioning
confidence: 99%
“…Empirical studies show that lonely adults are often more withdrawn than their nonlonely peers (Watson & Nesdale, 2012), avoid others (Nurmi, Toivonen, SalmelaAro, & Eronen, 1997), and are more passive in social interactions ( Jones, Hobbs, & Hockenbury, 1982). Crosssectional and experimental research in which loneliness was induced showed that transient loneliness was associated with higher levels of shyness and fear of negative evaluation ( J. T. Cacioppo et al, 2006).…”
Section: The Behavioral Reaffiliation Process Across Ontogenymentioning
confidence: 99%